2013
DOI: 10.1590/s1516-89132013000300019
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium reduction by immobilized cells of Bacillus sphaericus AND 303

Abstract: Bacillus sphaericus AND 303, a Cr(VI)-resistant and reducing bacterium reported from serpentine outcrops of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…c. Immobilized cell technique in this technique, bacterial cells or enzymes are fixed to some polymer matrix such as polyacrylamide, polyester, polyurethane, diatomite, agar-agar, agarose and gelatine via chemical or physical methods (Pal et al 2013;Elangovan et al 2009). Immobilized cell techniques have many advantages like (1) being cost effective as cells/enzymes are reusable, (2) providing high product yields as it allows for high cell density in small space, (3) protection from shear forces, and (4) providing improved operational stability (Elangovan et al 2009;Zhu 2007).…”
Section: Bioreactor Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…c. Immobilized cell technique in this technique, bacterial cells or enzymes are fixed to some polymer matrix such as polyacrylamide, polyester, polyurethane, diatomite, agar-agar, agarose and gelatine via chemical or physical methods (Pal et al 2013;Elangovan et al 2009). Immobilized cell techniques have many advantages like (1) being cost effective as cells/enzymes are reusable, (2) providing high product yields as it allows for high cell density in small space, (3) protection from shear forces, and (4) providing improved operational stability (Elangovan et al 2009;Zhu 2007).…”
Section: Bioreactor Techniquesmentioning
confidence: 99%
“…Immobilized cell techniques have many advantages like (1) being cost effective as cells/enzymes are reusable, (2) providing high product yields as it allows for high cell density in small space, (3) protection from shear forces, and (4) providing improved operational stability (Elangovan et al 2009;Zhu 2007). Several studies have been reported to use immobilized cell and the cell-free enzyme extract of various bacteria for bioremediation of chromium from contaminated water and wastewater (Camargo et al 2003;Pal et al 2013;Elangovan et al 2009;Tekerlekopoulou et al 2013).…”
Section: Bioreactor Techniquesmentioning
confidence: 99%
“…It was observed that Cr(VI) removal by the immobilised consortium increased when increasing the initial metal concentration, but was incomplete with any assayed condition (Figure 2). Similarly, other immobilised bacterial strains achieved better results in Cr(VI) removal upon being exposed to higher concentrations of the metal [16,25]. This performance has been related to the diffusion of contaminants inside the matrix, which depends mostly on the concentration of the substance to be internalised.…”
Section: Effect Of Initial Cr(vi) Concentration On Simultaneous Removmentioning
confidence: 99%
“…A common characteristic of immobilised systems is that their remediation efficiency diminishes over time, mostly when they are used for the removal of metals [16,25,35,36]. This behaviour has been associated with increased mechanical instability and gradual cell leakage from the beads during reutilisation cycles [37].…”
Section: Stability and Reusability Of Immobilised Cellsmentioning
confidence: 99%
See 1 more Smart Citation